Հայաստան-Իրան տնտեսական հարաբերությունները (1991-2008 թթ.) - Պետրոսյան, Լուսինե (YSU Journal of International Affairs, 2016)
The development of economic relations with Iran has always been an active part of Armenia's foreign policy agenda. In the conditions of dual blockade, Iran is important as a transit country for Armenia. On the other hand, the strengthening of economic ties with Iran allows having some alternatives in the energy sector. Armenia also has some economic importance for Iran. It ultimately depends on the implementation of energy transit projects, as well as the necessity of realization of Iran's traditional interests in the region. Today, the role of locomotive between the relations of two countries continues to take economic direction. Moreover, these relations have a tendency to become larger cooperation. The Armenian-Iranian economic relations prepared a solid foundation for further development of political relations between the two countries.
Keywords: regional development, economic cooperation and unblocking, energy and transportation infrastructure projects, transit country